The Role of Social Services in Improving Community Welfare in Gayo Lues District (Study of Elderly Welfare) - Hamdan Hamdan; Heri Kusmanto; Adam Adam; Rudi Salam Sinaga (Budapest International Research and Critics University, 2021)
The purpose of this study is to analyze how the role of the Social Service in improving the welfare of the community, especially the elderly in Gayo Lues Regency and to find out the obstacles or constraints of the Social Service in carrying out its role in improving the welfare of the community, especially the elderly. The research method used in this research is descriptive with qualitative analysis. Data collection was obtained from interviews, observations, documentation and literature studies. The results of this study indicate that the role of the Social Service of Gayo Lues Regency in improving the welfare of the community, especially the elderly, has been implemented but has not been optimal. This can be seen from the various obstacles or obstacles faced by the Social Service, including the minimal program budget to support the program, inadequate human resources in carrying out activities so that the services carried out are not optimal and the difficulty in providing services due to limited facilities and infrastructure. The suggestion from this research is that the Social Service of Gayo Lues Regency makes a strategy in the form of an activity program that can absorb the budget in improving the welfare of the community, especially the elderly, developing human resources through training, education, coaching, budgeting for financing in the form of facilities and infrastructure for officers who carry out services for the community Elderly.